Effectiveness of Health Education Message in Improving Tetanus Health Literacy among Women of Childbearing Age: A Quasi-Experimental Study - Mujtaba Haider Bukhari, Khushbakht, Aashi Mughal, Ahsan Tariq, Maria Yaseen, Tamanna Fayyaz, Mujtaba Haider Bukhari, Khushbakht, Aashi Mughal, Ahsan Tariq, Maria Yaseen, Tamanna Fayyaz (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Pakistan is one of the 34 countries yet to achieve the neonatal tetanus global elimination target set by the World Health Organization. Lack of vaccination, inadequate knowledge about prevention and unsafe practices are major causes of spread. The study aims to determine the effectiveness of health education messages in improving tetanus health literacy among women of age 16 to 45 years. Material and Methods: The quasi-experimental study which was carried out from April 2018 to June 2018 at Holy Family Hospital, Rawalpindi consisted of 150 female respondents of age 16 to 45 years selected by nonprobability convenience sampling. Written informed consent was taken from each participant. Afterwards, respondents were sequentially delivered pre-test proforma, health education message (verbally and in the form of pamphlet), and a post-test proforma after a gap of 2 days. The pre-test and post-test proformas assessed knowledge about tetanus. Data were analyzed via SPSS version 22. Results: Out of 150 women 20.1% were uneducated and 79.9% were educated. Area of residence was urban for 83.3% and rural for 16.7%. Mean tetanus health literacy scores increased significantly from 6.32 ± 2.85 to 10.55 ± 3.87 (p=0.01). Health education message was more effective for students and employees compared with housewives (p=0.01). Similarly, women possessing higher education were more likely to have high scores on post-tests (p=0.01). Conclusion: The health education message is effective in improving tetanus health literacy among women. Keywords: Tetanus, Health literacy, Intervention.